2005
DOI: 10.1111/j.1349-7006.2005.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of dietary monoglucosylceramide 1‐O‐β‐glucosyl‐N‐2′‐hydroxyarachidoyl‐4,8‐sphingadienine on two different categories of colon preneoplastic lesions induced by 1,2‐dimethylhydrazine in F344 rats

Abstract: Sphingolipids display a wide spectrum of biological activities, including cell growth, differentiation and apoptosis. However, precise mechanisms by which these compounds exert anticancer or cancer-preventive effects are not known. In the present study, we evaluated the preventive efficacy of enriched dietary monoglucosylceramide 1-O-β β β β-glucosyl-N-2′ ′ ′ ′-hydroxyarachidoyl-4,8-sphingadienine (G 1 CM) on 1,2-dimethylhydrazine (DMH)-induced aberrant crypt foci (ACF) and β β β β-catenin-accumulated crypt (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
(47 reference statements)
2
27
0
Order By: Relevance
“…Our previous studies have shown that defective AARGC is associated with increased risk for CRC in p53 +/ -and p53 -/ -mice [28,29], and that up-regulation of AARGC by a variety of dietary agents and drugs is associated with protection for CRC [29, 35, 48 -52]. In keeping with earlier studies [5,34,47], our study showed that SM intake (0.05 -0.1%) did not affect baseline apoptosis. Furthermore, it did not increase AARGC or apoptosis in tumours nor did it restore defective AARGC characteristic of p53 +/ -mice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our previous studies have shown that defective AARGC is associated with increased risk for CRC in p53 +/ -and p53 -/ -mice [28,29], and that up-regulation of AARGC by a variety of dietary agents and drugs is associated with protection for CRC [29, 35, 48 -52]. In keeping with earlier studies [5,34,47], our study showed that SM intake (0.05 -0.1%) did not affect baseline apoptosis. Furthermore, it did not increase AARGC or apoptosis in tumours nor did it restore defective AARGC characteristic of p53 +/ -mice.…”
Section: Discussionsupporting
confidence: 89%
“…Lemonnier et al [34] showed that dietary intake of SM normalized apoptosis, but not beyond the level of control group. Other studies have shown no difference between the number of apoptotic cells in the colonic epithelium of control and SM diet [5,34,47]. With respect to the potential of dietary SM on preventing tumour initiation, our particular interest was to examine whether SM regulated the apoptotic response to DNA damage (AARGC), which is important for eliminating DNA-damaged cells during tumour initiation [35].…”
Section: Discussionmentioning
confidence: 99%
“…Rice bran inhibits the growth of human colon cancer cells [85], and rice bran consumption reduces the number of intestinal adenomas in APC Min mice, an animal model of human familial adenomatous polyposis (FAP) [86]. Finally, DMH-and AOM-induced preneoplastic lesions are inhibited by rice bran-derived sphingolipids in the colons of rats [87,88].…”
Section: Anti-cancer Effect Of Rice By-productsmentioning
confidence: 96%
“…For example, the dietary intake of glucosylceramide prevents colon preneoplastic lesions [15] and head and neck cancers [16,17]. Also, when administered to the skin, it improves skin disorders [18].…”
Section: Introductionmentioning
confidence: 99%